Put First Nations First - Staging Australian Women's Lives research team and Sydney focus group participants (2022)
Posters naming and describing tactics theatre makers use to address gender and gender-based oppression on stage and off between 1970-2022. Posters list practitioners known for using/developing the tactic anfd hashtags describing the tactic and link to their AusStage profiles.